29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 3 2010
DOI: 10.1115/omae2010-20730
|View full text |Cite
|
Sign up to set email alerts
|

On Sea Experiment of a Hybrid SPAR for Floating Offshore Wind Turbine Using 1/10 Scale Model

Abstract: This study aims at development of a cost-effective floating offshore wind turbine. The proto-type model considered herein is composed of 1) 2MW horizontal-axis wind turbine (HAWT) of down-wind type, 2) steel mono-tower with 55m hub height above sea level, 3) steel-prestressed concrete (PC) hybrid SPAR-type foundation with 70m draught, and 4) catenary mooring system using anchor chains. In order to demonstrate the feasibility of the concept, on-sea experiment using a 1/10 scale model of the prototype has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The detailed specifications will be given later; however, the state-of-the-art specifications are followed. The experimental validation is necessary in order to apply the developed code for structural design of a real structure, Utsunomiya et al, [7][8][9] have, thus, made a series of experiments, and the developed code has been validated against these experimental results. However, these experiments do not cover the cases where wind, wave, and current are applied at the same time and the vertical fins for mitigation of yaw motion (stated later) are equipped.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed specifications will be given later; however, the state-of-the-art specifications are followed. The experimental validation is necessary in order to apply the developed code for structural design of a real structure, Utsunomiya et al, [7][8][9] have, thus, made a series of experiments, and the developed code has been validated against these experimental results. However, these experiments do not cover the cases where wind, wave, and current are applied at the same time and the vertical fins for mitigation of yaw motion (stated later) are equipped.…”
Section: Introductionmentioning
confidence: 99%
“…Due to spar buoy's excellent stability and after continuous theoretical studies and site monitoring, the Hywind concept has eventually been commercialized in the world's first floating wind farm: Hywind Scotland [25], in 2017, which is a milestone in the offshore wind turbine history. Utsunomiya [26][27][28] also proposed a hybrid spar type FOWT. The lower part of the spar platform was made of prestressed concrete composed of precast segments and the upper part was made of steel in order to reduce the platform construction cost.…”
Section: Introductionmentioning
confidence: 99%
“…Utsunomiya et al 6 reported experiments of a 1/10 scale model wind turbine on a Spar-type foundation installed 30 m from the quay of Sasebo shipbuilding yard in Japan. The main focus of this study was the dynamics of the substructure, and the applied wind turbine was chosen as a conventional micro wind turbine.…”
mentioning
confidence: 99%